Small Activating RNA Modulation of the G Protein‐Coupled Receptor for Cancer Treatment. Issue 26 (16th June 2022) - Xiong, Yunfang; Ke, Ran; Zhang, Qingyu; Lan, Wenjun; Yuan, Wanjun; Chan, Karol Nga Ieng; Roussel, Tom; Jiang, Yifan; Wu, Jing; Liu, Shuai; Wong, Alice Sze Tsai; Shim, Joong Sup; et al.
Abstract: G protein‐coupled receptors (GPCRs) are the most common and important drug targets. However, >70% of GPCRs are undruggable or difficult to target using conventional chemical agonists/antagonists. Small nucleic acid molecules, which can sequence‐specifically modulate any gene, offer a unique opportunity to effectively expand drug targets, especially those that are undruggable or difficult to address, such as GPCRs. Here, the authors report  for the first time that small activating RNAs (saRNAs) effectively modulate a GPCR for cancer treatment. Specifically, saRNAs promoting the expression of Mas receptor (MAS1), a GPCR that counteracts the classical angiotensin II pathway in cancer cell proliferation and migration, are identified. These saRNAs, delivered by an amphiphilic dendrimer vector, enhance MAS1 expression, counteracting the angiotensin II/angiotensin II Receptor Type 1 axis, and leading to significant suppression of tumorigenesis and the inhibition of tumor progression of multiple cancers in tumor‐xenografted mouse models and patient‐derived tumor models. This study provides not only a new strategy for cancer therapy by targeting the renin‐angiotensin system, but also a new avenue to modulate GPCR signaling by RNA activation. Abstract : Small activating RNAs (saRNAs) targeting MAS1, delivered by an amphiphilic dendrimer (AD) vector, enhance MAS1 expression and counteract the angiotensin II pathway in cancer cells, leading to significantly suppressed tumorigenesis and inhibited tumor progression. This saRNA approach opens a new avenue of using saRNA to target undruggable G protein‐coupled receptors for drug development and disease treatment.